Presentación atípica de un síndrome de Gitelman: reporte caso: Atypical presentation of Gitelman's syndrome: case report - Neira-Ruiz, Laura Carolina (2023)
Gitelman syndrome is a rare pathology with prevalence of 25 cases per million habitants, though, the prevalence of heterozygotes is approximately 1% in the caucasian population. This is caused by an alteration in the expression of the Na+/Cl cotransporter sensitive to thiazides, which generates a series of characteristic hydroelectrolytic alterations, but with non-specific symptoms. We present the case of a 37-year-old woman who presented with of novo convulsive syndrome in which severe and refractory hypokalemia was documented accompanied by metabolic alkalosis, hypomagnesemia and hypocalciuria, being diagnosed with Gitelman syndrome. Since potassium disorders are common in emergency departments, it is important not to overlook this syndrome in the differential diagnosis of persistent hypokalemia, even in atypical presentations.